Investigation of the profilogram structure of microstrip microwave modules manufactured using additive 3D-printing technology - D. S. Vorunichev; M. S. Kostin (Российский технологический журнал)
Objectives. The aim of the work is to study the surface roughness of the current-carrying topology and dielectric of the upper (Top Layer) and lower (Bottom Layer) sides of microwave modules manufactured using additive three-dimensional printing technology when prototyping prototypes of microwave modules on a 3D printer of DragonFly 2020 LDM multilayer printed circuit boards.Methods. Methods of metallographic analysis in bright and dark fields, surface roughness profiling, and computer modeling were used.Results. Experimental samples of microstrip microwave elements of modules of multilayer boards of a given configuration, telemetry sensors, printed circuit board (PCB) antennas were obtained. The topological and radiophysical features of the additively formed upper and lower surface layers of experimental samples of boards of strip modules were studied. Optical profilogram measurements of the roughness of the outer sides of the board were carried out at 10 points, amounting to 2 µm for the upper layer of the topology and 0.3 µm for the lower layer; the average grain size of the dielectric base was determined at 0.007 mm2. The roughness of the conductive topology and upper side dielectric was shown to correspond to an accuracy class of 6–7, while the roughness of the microstrip conductive topology and the dielectric of the lower side of the board corresponds to an accuracy class of 10–12.Conclusions. It is established that an uneven formation of the lower and upper strip layers of the printed module can affect the inhomogeneity of the distribution of radiophysical parameters (dielectric permittivity, surface conductivity, etc.), as well as the instability of the structural (adhesion ability, thermal conductivity, etc.) characteristics of the strip module, which must be taken into account when prototyping devices using inkjet 3D printing technology, including when adapting Gerber projects of PCB modules created for classical board production technology.